Exploratory study of single and multi-step dissolution-precipitation synthesis of carbonate containing hydrocalumite - Labuschagne, F.J.W.J. (Frederick Johannes Willem Jacobus) (University of Pretoria, 2016)
Dissertation (MEng)--University of Pretoria, 2015.